Fighting Viral Infections and Virus-Driven Tumors with Cytotoxic CD4+ T Cells - Muraro, Elena; Merlo, Anna; Martorelli, Debora; Cangemi, Michela; Dalla Santa, Silvia; Dolcetti, Riccardo; Rosato, Antonio (Frontiers in Immunology, 2017)
CD4+ T cells have been and are still largely regarded as the orchestrators of immune responses, being able to differentiate into distinct T helper cell populations based on differentiation signals, transcription factor expression, cytokine secretion, and specific functions. Nonetheless, a growing body of evidence indicates that CD4+ T cells can also exert a direct effector activity, which depends on intrinsic cytotoxic properties acquired and carried out along with the evolution of several pathogenic infections. The relevant role of CD4+ T cell lytic features in the control of such infectious conditions, is also leading to their exploitation as a new immunotherapeutic approach. This review aims at summarizing currently available data about functional and therapeutic relevance of cytotoxic CD4+ T cells in the context of viral infections and virus-driven tumors.